Pengaruh Etika dalam Praktik Akuntansi terhadap Kepercayaan Publik - Annisa Fitriah Mudassir (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Ethics in accounting practice is a fundamental aspect that plays a crucial role in building, maintaining, and enhancing public trust in financial statements and the information presented by companies. In an increasingly complex and competitive business context, where transparency and accountability are paramount, the application of professional ethical principles by accountants not only contributes to the integrity of financial reports but also influences the perceptions and trust of stakeholders, including investors, creditors, and the general public. This article delves deeply into the impact of accountants' professional ethics on public perception and how the application of ethical principles can enhance the integrity of financial statements. Through a qualitative approach involving in-depth interviews with accountants, financial managers, and stakeholders across various industries, this research identifies factors that support and hinder the application of ethics in accounting practice. The study also explores how organizational culture, ethics education, and regulations play a role in shaping accountants' ethical behavior. The findings indicate that the strong application of ethics in accounting practice significantly contributes to the enhancement of public trust. This trust, in turn, positively impacts the reputation of the company, which is crucial for long-term business sustainability. Furthermore, this article identifies the challenges faced by accountants in applying ethical principles, including pressure from management to present more favorable financial reports and the lack of adequate ethics education in accounting curricula. Thus, this article aims to provide valuable insights for practitioners, academics, and policymakers regarding the importance of ethics in accounting as a foundation for creating trustworthy financial statements. Additionally, the article recommends the need for improved ethics education in accounting educational institutions and the strengthening of regulations that encourage the application of higher ethical standards in accounting practice. With these measures, it is expected that public trust in financial statements can continue to be enhanced, supporting better decision-making by stakeholders and ultimately strengthening the foundation of a more transparent and accountable economy.